Dialectics and International Hegemonism in the Discourse of Trump on COVID-19 - Lecturer. Hussein Abdulkareem Jajob; Asst. Prof PhD. Ali Abdulhameed Faris Al-assadi (مجلة اداب ذي قار, 2022)
The present study was an attempt to bridge the gap between political discourse, Critical Discourse Analysis (CDA), and COVID-19 which can be considered as the most recently contentious social event in the contemporary history of the world. It aimed to identify the relationships between language and identity and to examine the dialectics of the international hegemony in the speech of the former American President Trump which was delivered to the United Nations General Assembly on Sept. 22, 2020. For achieving the objectives of this study, Fairclough’s (2001) Dialectical Ways of Social Practices and Halliday’s (1985) SFG were adopted. The study arrived at certain conclusions which could be summed up as the following: I. via ideational and interpersonal metafunctions, the American national identity was disclosed as the most prominent theme in the whole speech; II. Interpersonal metafunctions of ‘Tense’, whereby the employment of present tense appeared to be more frequent (11 times) than the past tense (7 times), helped reveal the embedded ideology of ‘Americanism’ or ‘exceptionalism’ as a social act and behavior; III. the ideology of ‘Americanism’ was also displayed by the interpersonal metafunctions of pronouns whereby the inclusive pronouns appeared to be more frequent (11 times) than the exclusive ones (1 time), IV. by-way-of the ideational and interpersonal metafunctions, the dialectical social practice of ‘Othering’ was defined; China and the WHO were identified to be the fundamental ‘Other’ for Trump, and V. the American hegemony as a dialectical social practice was revealed through the interpersonal metafunction of the modal verb ‘must’.